Interhemispheric transcallosal transchoroidal approach for resection of a mesencephalic lesion - Lucas Pires Augusto; Matheus Fernando Manzolli Ballestero; Ricardo Santos de Oliveira (Brazilian Society for Pediatric Neurosurgery, 2019)
A 12 years old boy presented with strabismus, left third nerve palsy (ptosis, mydriasis, downward and abducted eye), and vertical conjugate gaze paresis. A brain magnetic resonance image revealed a brainstem solid cystic tumor in the mesencephalic tegmentum, with compression of the aqueduct of Sylvius and associated supratentorial ventriculomegaly. The patient underwent an interhemispheric transcallosal transchoroidal approach for a subtotal resection of the mesencephalic periaqueductal lesion. The pathology report was a low grade neuroepithelial tumor. The patient evolved with no new neurological deficits.